Extreme temperatures increase the risk of pediatric pneumonia: a systematic review and meta-analysis - Makrufardi, Firdian; Triasih, Rina; Nurnaningsih, Nurnaningsih; Chung, Kian Fan; Lin, Sheng-Chieh; Chuang, Hsiao-Chi (Frontiers in Pediatrics, 2024)
The impact of climate change on ambient temperatures threatens to worsen pediatric pneumonia-related outcomes considerably. This study examined the associations of temperature variation and extreme temperature with pediatric pneumonia-related events using a meta-analysis. We systematically searched PubMed, Medline, Embase, and Web of Science databases for relevant literature, and the quality of evidence was assessed. Fixed and randomeffects meta-analyses were performed to calculate the pooled relative risks (RRs) of the associations with pneumonia-related events. We observed that a 1°C temperature variation increased the RR of pneumonia events by 1.06-fold (95% confidence interval (CI): 1.03-1.10).A 1°C temperature variation increased the RR by 1.10-fold of the pediatric pneumonia hospital admissions (95% CI: 1.00-1.21) and 1.06-fold of the pediatric pneumonia emergency department visits (95% CI: 1.01-1.10). Extreme cold increased the RR by 1.25-fold of the pediatric pneumonia events (95% CI: 1.07-1.45). A 1°C temperature variation increased the RR of pneumonia events in children by 1.19-fold (95% CI: 1.08-1.32), girls by 1.03-fold (95% CI: 1.02-1.05), and in temperate climate zones by 1.07-fold (95% CI: 1.03-1.11). Moreover, an increase in extreme cold increased the RR of pneumonia events in children by 2.43-fold (95% CI: 1.72-3.43), girls by 1.96-fold (95% CI: 1.29-2.98) and in temperate climate zones by 2.76-fold (95% CI: 1.71-4.47). Our study demonstrated that pediatric pneumonia events are more prevalent among children, particularly girls, and individuals residing in temperate climate zones. Climate change represents an emergent public health threat, affecting pediatric pneumonia treatment and prevention.